Assessment of the infectious diseases surveillance system of the Republic of Armenia: an example of surveillance in the Republics of the former Soviet Union - Mac Kenzie William R; McNabb Scott JN; Davidiants Vladimir; Wuhib Tadesse; Chorba Terence L (BMC, 2002)
Abstract Background Before 1991, the infectious diseases surveillance systems (IDSS) of the former Soviet Union (FSU) were centrally planned in Moscow. The dissolution of the FSU resulted in economic stresses on public health infrastructure. At the request of seven FSU Ministries of Health, we performed assessments of the IDSS designed to guide reform. The assessment of the Armenian infectious diseases surveillance system (AIDSS) is presented here as a prototype. Discussion We performed qualitative assessments using the Centers for Disease Control and Prevention (CDC) guidelines for evaluating surveillance systems. Until 1996, the AIDSS collected aggregate and case-based data on 64 infectious diseases. It collected information on diseases of low pathogenicity (e.g., pediculosis) and those with no public health intervention (e.g., infectious mononucleosis). The specificity was poor because of the lack of case definitions. Most cases were investigated using a lengthy, non-disease-specific case-report form Armenian public health officials analyzed data descriptively and reported data upward from the local to national level, with little feedback. Information was not shared across vertical programs. Reform should focus on enhancing usefulness, efficiency, and effectiveness by reducing the quantity of data collected and revising reporting procedures and information types; improving the quality, analyses, and use of data at different levels; reducing system operations costs; and improving communications to reporting sources. These recommendations are generalizable to other FSU republics. Summary The AIDSS was complex and sensitive, yet costly and inefficient. The flexibility, representativeness, and timeliness were good because of a comprehensive health-care system and compulsory reporting. Some data were questionable and some had no utility.